2023
DOI: 10.1038/s41598-023-31993-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Effectiveness of ultrasound guided dry needling in management of jumper’s knee: a randomized controlled trial

Abstract: Jumper’s knee is highly prevalent condition in athletes. Very limited evidence is available on clinical effects of tendon dry needling. Therefore, the objective of this study is to compare the effects of ultrasound-guided dry needling (UG-DN) combined with conventional physical therapy and conventional physical therapy alone in patients with jumper’s knee. A total of 96 patients with pre-diagnosed jumper’s knee were randomly assigned to experimental group (UG-DN + CPT) and conventional group (CPT alone) with 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Research has shown that proximal tibia fractures are the most common, accounting for approximately 1% of all fractures, and are mainly caused by high-energy trauma, especially in men [41] . Severely comminuted fractures, complete articular fractures, and malalignment of the joint increase the incidence of KOA [42] . Although surgery may restore normal knee function, 35% of patients may develop signs and changes of KOA within 14 years of surgery and may resort to total knee arthroplasty as a secondary treatment [43] .…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that proximal tibia fractures are the most common, accounting for approximately 1% of all fractures, and are mainly caused by high-energy trauma, especially in men [41] . Severely comminuted fractures, complete articular fractures, and malalignment of the joint increase the incidence of KOA [42] . Although surgery may restore normal knee function, 35% of patients may develop signs and changes of KOA within 14 years of surgery and may resort to total knee arthroplasty as a secondary treatment [43] .…”
Section: Discussionmentioning
confidence: 99%
“…They were randomized and quasi-randomized controlled clinical trials (n = 6) published from 2012 to 2023. The studies were conducted in Greece [25], USA [33], India [24], Spain [21,34] and Pakistan [35]. They were randomized and quasi-randomized controlled clinical trials (n = 6) published from 2012 to 2023.…”
Section: Study Selectionmentioning
confidence: 99%
“…They were randomized and quasi-randomized controlled clinical trials (n = 6) published from 2012 to 2023. The studies were conducted in Greece [25], USA [33], India [24], Spain [21,34] and Pakistan [35].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations